FO system for high-level concentration of liquids by dehydration without heating or pressurisation. Issue 4 (April 2019) - Atkinson, Simon
Abstract : Chemicals and materials science company Asahi Kasei Corp has developed a forward osmosis membrane system for the high-level concentration of liquids without heating or pressurisation. This brief article highlights the technology, which is targeted at the food and pharmaceutical industries.